TEXT-BASED LEARNING (TBL) TO ACTIVATE ADULT EFL LEARNERS IN LEARNING ENGLISH: A NARRATIVE INQUIRY - Iftanti, Erna (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
In response to the fact that college students complain on their unsuccessful story of their EFL learning experience such as the limited number of vocabulary, English Grammar confusion, low competence of English language skills, this article explores an alternative effective way of helping them to improve their English through Text-Based Learning (TBL) model. This article is then intended to narrate the implementation of TBL to teach English for college students of non English Department of Post Graduate Program of State Islamic Institute of Tulungagung, Indonesia. The result of implementing this teaching model proves to be able to not only stimulate joyful learning atmosphere but to attract the studentsâ active participation during the EFL instructional process as well. This further brings about their better practical understanding on English language skills as their expectation. Therefore, for English lecturers, this model is pedagogically good to be implemented in their English instructional practices.